HUBUNGAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA LANGSUNG DI KABUPATEN ACEH UTARA - Syamni, Ghazali; Husodo, Zaafri; din, Syarifuddin (JURNAL KEBANGSAAN, 2014)
The objectives this research is to analyze the relationship legal revenue to expenditures in North Aceh. The data used in this study are reported revenue realization consisting of local taxes, retribution, and other legal revenue to particular expenditure direct in North Aceh for 30 years from 1982 -2011. The method used in this study is multiple regression analysis. The results found that the revenue associated with direct expenditure in the North Aceh. This indicates that the higher the revenue, the greater the direct spending by an area. Subsequently other findings in this study are all components of tax revenue in this case, retribution, etc. legitimate income also affect direct spending. These findings indicate the government of the district or other government in Indonesia to be more active in raising revenue. But in the process of determination procedures or approaches that investment pro investment.Keywords: relationship, legal revenue, expenditures, north Aceh